2019
DOI: 10.1155/2019/1263629
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Oxidative Stability and Microbial Shelf Life of Vanilla Cake by Coconut Oil Meal and Sesame Oil Meal Phenolic Extracts

Abstract: Phenolic extracts of coconut oil meal (CME) and sesame oil meal (SME) were compared with synthetic antioxidants for the potential of improving shelf life of vanilla cake. CME maintained hexanal (product of chemical spoilage) levels below 0.3 mg/kg in cake up to 14 days. BHT- and SME-added cakes maintained hexanal levels below 2 mg/kg, while control cake with no added antioxidants exceeded this level by day 14. Both CME and SME extended the microbial shelf life up to 13 days, while control and BHT-added cake ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The TPC was previously reported as 90.1-121.5 mg/ kg for pumpkin seed by-products by Balbino et al (2019) and 3.49-55.52 mg/g for pumpkin seed. The phenolic contents of coconut meal were studied by Senanayake et al (2019) and reported to be 775 mg GAE/ kg. The TPC and Different results in the literature could be due to different extraction methods and cultivars (Tavarini et al, 2019).…”
Section: The Bioactive and Antimicrobial Properties Of By-productsmentioning
confidence: 99%
“…The TPC was previously reported as 90.1-121.5 mg/ kg for pumpkin seed by-products by Balbino et al (2019) and 3.49-55.52 mg/g for pumpkin seed. The phenolic contents of coconut meal were studied by Senanayake et al (2019) and reported to be 775 mg GAE/ kg. The TPC and Different results in the literature could be due to different extraction methods and cultivars (Tavarini et al, 2019).…”
Section: The Bioactive and Antimicrobial Properties Of By-productsmentioning
confidence: 99%
“…The interest in the phenolic substances in coconut oil is also due to their antioxidant activity and related health benefits (Seneviratne et al, 2011;Lima et al, 2015;Narayanankutty et al, 2018;Rohman et al, 2021;Senanayake et al, 2021). In addition, the phenolic compounds present in coconut oil and coconut oil meal improve the shelf-life of coconut oil as well as other edible oils and baked food (Senanayake et al, 2019). Even though there is a wealth of literature regarding research conducted on the phenolic substances of olive oil and other common edible oils, the first report on the phenolic substances in coconut oil was published in 2008 (Seneviratne and Dissanayake, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding values for the standard were 16.6, 46.8, 17.5 and 3.4 mg/mL. The extent of inhibition of bacteria by the coconut meal films depends on the phenolic levels and the interaction between the microorganisms and the substrate 23 . Also, the films were able to inhibit the 2 gram positive bacteria to a greater extent than the other 2 gram negative bacteria.…”
Section: Resultsmentioning
confidence: 92%
“…The extent of inhibition of bacteria by the coconut meal films depends on the phenolic levels and the interaction between the microorganisms and the substrate. 23 Also, the films were able to inhibit the 2 gram positive bacteria to a greater extent than the other 2 gram negative bacteria. It has been reported that Gram-negative bacteria have a tough outer protective layer which is difficult to penetrate and hence have higher resistance to the films.…”
Section: Antibacterial Activity and Antioxidant Potentialmentioning
confidence: 92%